Consciousness of Racial Equality as Reflected in Michael Jackson’s “Black or White” - Kirana, Devi (LANTERN (Journal on English Language, Culture and Literature), 2014)
In a revealing expression and feeling, the author uses an analysis with the meaning of the lyrics of the song created. This final paper contains about racial equality described in the lyrics of Michael Jackson's "Black or White". The writer interests in discussing racial equality because this topic is very important among people of color, especially this has been experienced by such famous pop singer Michael Jackson who used to be blacks. This discussion intends to illustrate the points of race equality expressed by Michael Jackson through the lyrics of the song "Black or White". The writer uses a method of library research, so the writer uses books or libraries, music and lyric scrutining, recording, articles, flash media interviews and additional references in the search on the internet to collect data. The analysis in this final paper raises the Popular Culture of Culturalism theory presented by John Storey. The result shows that Michael Jackson expresses his feelings against the differences between races, especially African-Americans in her private life through a piece of song lyrics.